Answer:
Simplifying
logx + -4 = 0
Reorder the terms:
-4 + glox = 0
Solving
-4 + glox = 0
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '4' to each side of the equation.
-4 + 4 + glox = 0 + 4
Combine like terms: -4 + 4 = 0
0 + glox = 0 + 4
glox = 0 + 4
Combine like terms: 0 + 4 = 4
glox = 4
Divide each side by 'lox'.
g = 4l-1o-1x-1
Simplifying
g = 4l-1o-1x-1
The first term is 5. The sequence goes by 2. And 23 is the 9th term. 9x2=18
23-18=5
Uhhh 18?? 9+9, 10+8, 7+11, 6+12, 5+13, 4+14, 3+15, 2+16, 1+17
1/2............................................ I hope this helps
Answer:
hmm ..
just transfer the X at the right side and others on left side
Step-by-step explanation:
so you get
w-z = yx
so later
(w-z)/y = x